The Influence of Learning Methods and Student Personality Types in Islamic Religion Lessons - Adri Lundeto (International Journal of Science and Society, 2021)
The learning educates pupils that the key predictors of academic success are educational concepts and learning theories. Learning is a double process of communication: the teacher as an educator teaches while students teach. This is a qualitative type of research. Qualitative research is an investigation process which produces descriptive data of people and observed conduct in written or spoken terms. An interdisciplinary strategy is applied in this study, integrating management, pedagogy, sociology and psychology techniques. Two types of data sources are used in this study: Primary data. Primary information. Primary data are collected in field research from informants who, in this case, are professors of Islamic Religious Education directly. Research and analytical results show that: 1) there have been difference between students who follow the co-operative method of learning and students who follow the conventional method of learning; 2) there has been no difference between students with introverted personality type and students with extraverted personality.